2001
DOI: 10.1103/physrevb.63.245416
|View full text |Cite
|
Sign up to set email alerts
|

Joint density of electronic states for one isolated single-wall carbon nanotube studied by resonant Raman scattering

Abstract: Resonant Raman scattering ͑RRS͒ measurements made with a tunable laser provide a highly reliable technique to study the shape of the joint density of electronic states ͑JDOS͒ of isolated single-wall carbon nanotubes ͑SWNTs͒. RRS can be used to determine the energy value for the one-dimensional ͑1D͒ van Hove singularities of a SWNT with a precision better than 5 meV, thereby providing important information that could be used for subsequent measurements on this same SWNT. With RRS, the measured width of the JDOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(93 citation statements)
references
References 22 publications
6
86
0
1
Order By: Relevance
“…Smaller broadening, on the other hand, was found in recent experiments by Jorio et al who determined the width of VHSs using resonant Raman scattering from individual SWNTs [ 50]. The latter authors report on very narrow features in the energy dependence of the resonant Raman signal with a broadening of the order of 0.1 meV to 1 meV.…”
Section: Internal Thermalization and E-e Interactionsmentioning
confidence: 67%
“…Smaller broadening, on the other hand, was found in recent experiments by Jorio et al who determined the width of VHSs using resonant Raman scattering from individual SWNTs [ 50]. The latter authors report on very narrow features in the energy dependence of the resonant Raman signal with a broadening of the order of 0.1 meV to 1 meV.…”
Section: Internal Thermalization and E-e Interactionsmentioning
confidence: 67%
“…This changed behavior may be explained by overlapping of energy bands in nanotube bundles. Scanning tunneling spectroscopy (Wildoer et al, 1998), resonant Raman scattering (Jorio et al, 2001) and optical absorption or emission measurements (Connell et al, 2002) confirmed the electronic DOS in carbon nanotubes. Ouyang et al (Ouyang et al, 2001) experimentally found a pronounced dip in the electronic DOS of a (8, 8) SWCNT at Fermi level inside a bundle, compared to an isolated tube.…”
Section: Characteristics Of a Bundle Of Three Different Types Of Swcntsmentioning
confidence: 82%
“…3. Knowing d t and E ii allowed the assignment of the measured SWNT as the (18, 0) metallic SWNT (Jorio et al 2001b). By doing the experiment with a tunable laser, one can measure the resonance line shape profile experimentally.…”
Section: Resonance Raman Spectroscopy Of Quasi-one Dimensional Carbonmentioning
confidence: 99%
“…3). Such an experiment was performed for a SWNT with ω RBM = 173.6 cm −1 , i.e., d t = 248/173.6 = 1.43 nm (Jorio et al 2001b). Very accurate values for E ii = 1.655 ± 0.003 eV and = 8 meV were found from Fig.…”
Section: Resonance Raman Spectroscopy Of Quasi-one Dimensional Carbonmentioning
confidence: 99%